2017
DOI: 10.1186/s12888-016-1157-2
|View full text |Cite
|
Sign up to set email alerts
|

A case of GABAR antibodies in schizophrenia

Abstract: BackgroundIn the last couple of years, schizophrenia was often discussed as autoimmune disease. Several antibodies were suspected, but so far there has been no proof of Gamma-aminobutyric acid (GABA) receptor antibodies in patients with schizophrenia.Case presentationIn this case report we present a 21-year old woman with schizophrenic symptoms, who showed anti-GABAB1 antibodies when screened by a vast recombinant neurology mosaic on Human Embryonic Kidney Cells 293 (HEK293) cells. The young woman presented wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Early identification of antibodies targeting neurotransmitter receptors, such as 5-hydroxytryptamine 1A receptor and muscarinic cholinergic receptor 1, as well as dopamine-2 receptor, in individuals with schizophrenia suggests that autoimmunity plays a role in a subgroup of these patients [ 14 16 ]. Notably, the recent discovery of antibodies against synaptic and neuronal cell membrane proteins such as anti- N -methyl- d -aspartate receptor (NMDAR) and gamma-aminobutyric acid beta receptor (GABA ß R) provides more direct evidence etiologically linking autoimmunity-related dysregulation of glutamatergic and GABAergic neurotransmissions to subsequent hazard of psychosis [ 17 23 ]. One meta-analysis showed that patient with psychiatric illnesses such as schizophrenia and schizoaffective disorders are about three times more likely to have NMDAR antibodies (mostly of IgA or IgM type against GluN1 (NR1) subunit), compared with healthy controls [ 24 ].…”
Section: Antibodies Against Neurotransmitter Receptors and Synaptic Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Early identification of antibodies targeting neurotransmitter receptors, such as 5-hydroxytryptamine 1A receptor and muscarinic cholinergic receptor 1, as well as dopamine-2 receptor, in individuals with schizophrenia suggests that autoimmunity plays a role in a subgroup of these patients [ 14 16 ]. Notably, the recent discovery of antibodies against synaptic and neuronal cell membrane proteins such as anti- N -methyl- d -aspartate receptor (NMDAR) and gamma-aminobutyric acid beta receptor (GABA ß R) provides more direct evidence etiologically linking autoimmunity-related dysregulation of glutamatergic and GABAergic neurotransmissions to subsequent hazard of psychosis [ 17 23 ]. One meta-analysis showed that patient with psychiatric illnesses such as schizophrenia and schizoaffective disorders are about three times more likely to have NMDAR antibodies (mostly of IgA or IgM type against GluN1 (NR1) subunit), compared with healthy controls [ 24 ].…”
Section: Antibodies Against Neurotransmitter Receptors and Synaptic Pmentioning
confidence: 99%
“… Psychosis associated with autoantibodies targeting well-characterized synaptic and neuronal cell surface proteins [ 3 5 ]. Indeed, findings from several case reports and clinical case series have linked autoantibodies targeting NMDAR, α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR), GABA ß R and VGKC-protein complex, to new-onset psychosis among other psychiatric disturbances (e.g., mania, anxiety, aggression, emotional lability, and personality changes) as the dominant presenting symptoms [ 17 23 , 27 , 38 – 42 ]. Although the majority of these patients eventually exhibit a wide constellation of neurological symptoms throughout the course of the illness, isolated neuropsychiatric symptoms with dominant psychosis may rarely remain the key symptoms; we suggest that the latter pattern might constitute the presentation of milder form or forme fruste of autoimmune encephalitis.…”
Section: Autoimmune Disorders Presenting With New-onset Psychotic Symmentioning
confidence: 99%
“…Several reviews highlight that music interventions during pregnancy also have a general anxiety reducing effect [ 50 , 80 , 84 ]. Moreover, studies have shown that music interventions among pregnant women have even specific positive effects in risk groups.…”
Section: Introductionmentioning
confidence: 99%
“…Distinct pathophysiological trajectories and compensational mechanisms might give rise to similar signs and symptoms and result in a single diagnostic label. For example, antibodies targeting GABARs, NMDARs or potassium ion channels can all lead to schizophrenia, as is also true for microdeletion in the 22q11.2 chromosomal band …”
Section: Discussion and Future Outlooksmentioning
confidence: 99%